Criminal Liability for Vigilantism Under Articles 351, 170, and 406 KUHP - Jamaludin; Dyah A, Tata Eliestiana; Sunardi, Heru; Tradesa, Anggi Purnama (Jurnal Ilmu Kepolisian, 2025)
This study was conducted with the aim of determining criminal liability for the crime of vigilantism (eigenrichting) in criminal law in Indonesia. This study uses a qualitative approach with an orientation towards a deep understanding of the phenomenology of the crime of vigilantism and the form of criminal liability for the perpetrators. Data analysis in this study was conducted using a qualitative legal analysis approach. The results of this study indicate that criminal liability for the crime of vigilantism (eigenrichting) is still enforceable under Indonesian criminal law. Everyone who commits the crime will undergo sanctions and cannot be represented by another person. Criminal liability for the crime of vigilantism (eigenrichting) is indeed not regulated in a limitative manner in the laws and regulations, however in the law there are elements of a crime as stated in the Criminal Code (KUHP), namely in Section 351 concerning Abuse, Section 170 concerning Abuse and Section 406 concerning Destruction. Therefore the perpetrators of the crime of vigilantism can be subject to several Sections above.